Seismic site classification and amplification of shallow bedrock sites - Panjamani, Anbazhagan (PLoS One, 2018)
This study attempts to develop empirical correlations between average penetration resistance ([Image: see text] ), averaged velocities over depth up to bedrock depth ([Image: see text] ) and 30 m ([Image: see text] ) for shallow depth sites (having bedrock at a depth less than 25 m). A total of 63 shallow sites were assessed for penetration resistance values up to the bedrock from Standard Penetration Tests (SPT) and dynamic soil property analysis, i.e., Shear Wave Velocity (V(S)) from Multichannel Analysis of Surface Waves. The study shows that 30 m averaged shear wave velocities are more than the average velocity up to bedrock depth in shallow bedrock sites because of inclusion of rock site velocity. Furthermore, averaged SPT-N([Image: see text] ) and average V(S) ([Image: see text] ) up to bedrock depth were correlated with the 30 m average([Image: see text] ) values. This is the first attempt in developing empirical relationships of this kind for seismic site classification. These correlations can be made useful for seismic site classification of sites in regions with Standard Penetration Test (N(SPT)) values and limited V(S) values. Further surface and bedrock motion recordings of 12 selected KiK-net shallow depth sites were collected and amplifications were estimated with the respective peak ground acceleration, spectral acceleration and thereby related to the average shear wave velocity up to bedrock and 30 m. The results show that the amplification is better correlated to the [Image: see text] than [Image: see text] for shallow depth sites, and more data can be added to strengthen this correlation.